SUPPLY CHAIN MANAGEMENT: A REVIEW - Mahmud Basuki (Journal of Industrial Engineering and Halal Industries, 2021)
Supply Chain Management (SCM) is a very dynamic upstream to downstream distribution system that aims to produce a service, a better product, and a minimum cost. To achieve this, there are new concepts for the development of SCM, namely Lean Supply Chain (LSC), Supply Chain Quality Management (SCQM), and Supply Chain Network Design. Where LSC applies lean to address waste in the distribution chain, maximizing production, so costs will be reduced, and competitiveness will increase. Whereas SCQM in its application has the term internal dimension, namely quality management and external dimension, namely the context of supply chain management. Then for supply chain network design is a technology that can support the development of SCM to realize the connectivity and integration of distribution data so that all parties must feel benefited, both the producers, the shipping service, and the end users.